Evaluation of One Health approach measures implemented in response to the human rabies outbreak in the Maxakali Indigenous Land, Brazil - Dilceu Silveira Tolentino Júnior; Maryana Santos Vasconcelos Marques; Jomar Otávio Zatti Pereira; Roberto Carlos de Oliveira (One Health Outlook)
Abstract Background This article presents and evaluates the One Health interventions implemented after a rabies outbreak in indigenous Maxakali children living in the Pradinho Village in the municipality of Bertópolis, Minas Gerais, Brazil, which occurred between April and May 2022, in the third month and in the first year after the event. Methods This was an evaluation study conducted using official documents. The One Health approaches implemented in response to the outbreak were assessed from the perspective of continuity and self-sustainability, in order to conjecture the tactical and strategic operational measures adopted. The One Health interventions were assessed based on the analysis of qualitative and quantitative data from observations and records of environmental, observational, and animal and human behavior samples. The coordination mechanisms between the Rabies Working Group of the Ministry of Health, composed of the National, State and District Strategic Information Centers for Health Surveillance, the Field Epidemiology Training Program, the Special Secretariat for Indigenous Health, the State Secretariat of Health of Minas Gerais, the Agricultural Institute of Minas Gerais, the Municipal Secretariats of Health and Environment of Bertópolis, hospitals in the region and the Fire Department of Minas Gerais were assessed. Results Training activities were carried out for health team professionals; a post-exposure prophylaxis scheme was implemented for susceptible contacts and a pre-exposure prophylaxis scheme was implemented by the vaccination team for all village residents; the animal anti-rabies vaccine was administered to 100% of the canine and feline population in Aldeia Pradinho, within a focal and perifocal radius of 3 to 5 km from the outbreak site. Approximately 100 households were inspected and natural and artificial roosts of sanguivorous bats were identified. An epidemiological survey was carried out in the region to verify attacks by sanguivorous bats on cattle and horses. The evaluation of the operational approaches in the 3rd month showed high efficacy, but after 1 year they were considered of low to medium efficacy. Evaluations of the tactical and strategic approaches after 1 year were considered of low efficacy due to the lack of self-sustainability. Conclusions One Health interventions were useful in addressing health challenges and consolidating partnerships. Although not all strategic response actions have proven to be self-sustainable after a year of this rabies outbreak that affected indigenous Maxakali children, gains were observed in terms of trust, community engagement, and intersectoral collaboration.